Optimizing The Supply Chain Management System Safety Equipment for Sea Vessels Increasing Company Productivity (Case Study of CV Bandar Bahari on Banjarmasin) - Bayu Satrya Nugraha; Zaenal Abidin; Paulus Raga; Muhammad Fahrudin (Journal of Economics and Management Scienties, 2026)
Supply chain efficiency is a key factor for companies in maintaining competitiveness and operational sustainability. CV Bandar Bahari, a provider of marine safety equipment, faces challenges arising from fluctuating demand for life jackets and other maritime safety products, which affect productivity and operational performance. This study aims to analyze supply chain performance, identify customer expectations in improving supply chain effectiveness, and formulate strategies for sustainable productivity improvement. This research employs a mixed-method approach with a case study design at CV Bandar Bahari. Qualitative data were collected through in-depth interviews, observations, and documentation studies involving internal parties directly engaged in supply chain activities, while quantitative data were obtained through questionnaires distributed to customers and supply chain partners. Data analysis was conducted using Interpretative Phenomenological Analysis (IPA) for qualitative data, as well as the Customer Satisfaction Index (CSI) and Importance–Performance Analysis (IPA) for quantitative data. The findings indicate that supply chain performance continues to face several constraints, including predominantly manual work systems, suboptimal technology utilization, limited human resources, and constraints in order picking and delivery due to route availability, resulting in longer lead times. This study emphasizes the importance of technology integration and human resource capacity development, including the management of environmental impacts. The proposed strategies focus on strengthening human resources and enhancing technology integration to achieve a sustainable supply chain management system at CV Bandar Bahari.